Monitoring Peringatan Dini Kebakaran Pada Sistem Smart Home Menggunakan NodeMcu Berbasis IoT - Kuncoro, Wahyu; Maulindar, Joni; Indah, Ratna Puspita (Universitas Nusantara PGRI Kediri, 2023)
Abstract – One of the most frequent disasters in Indonesia is fire. There are situations where homeowners are not aware that their house is on fire, such as when the owner is not home or at night when the owner is sleeping. Lack of information regarding the condition of a house that has caught fire can result in enormous material losses or can endanger a person's life if the fire is not resolved immediately. In this case, it is necessary to have a monitoring system that can provide information regarding the presence of early fire symptoms that can be accessed anytime and anywhere. This system will later be able to display fire, smoke, and temperature values from sensor readings that have been stored in the Firebase Realtime Database which will later be displayed on Mobile Apps. If there is a fire there will be a warning in the form of a buzzer and notification on the smartphone and the system will spray water through the waterpump. The results of this study are a fire early warning monitoring system on a smart home system using Internet of Things (IoT) based NodeMcu. It is hoped that this system can reduce or minimize the occurrence of fires and losses due to fires.